PREVALENCE AND ASSOCIATED FACTORS OF MALNUTRITION AMONG EARLY ADOLESCENT GIRLS IN SELECTED URBAN AND RURAL SCHOOLS OF WEST BENGAL - Kundu, Mousumi; Khan, Madhusree (International Journal of Research -GRANTHAALAYAH, 2025)
Introduction Adolescence is a period of rapid growth and development, acquisition of health-related behaviours such as food preferences and physical activity and these behaviours track throughout the life course and may contribute to the nutrition related to non- communicable diseases in adulthood. Aim: The aim of the study is to assess prevalence and associated factors of malnutrition among early adolescent girls. Method: the investigator conducted a descriptive comparative study on prevalence and associated factors of malnutrition among early adolescent girls in urban and rural schools of West Bengal with the objective to assess the prevalence of malnutrition and associated factors of malnutrition among early adolescent girls, to compare the prevalence of malnutrition between early adolescent girls in urban and rural schools and to find out the association between prevalence of malnutrition with selected associated factors of malnutrition among early adolescent girls in selected urban and rural schools of West Bengal. This study was based on “Nursing Process Model” developed by Ida Jean Orlando in 1958. Non-probability purposive sampling technique was adopted to select 140 participants. The tools used for the study were semi structured interview schedule to collect socio – demographic data, anthropometric measurement Proforma to assess the prevalence of malnutrition through the WHO z-score (BMI-For-age Girls 5 to 19 years) and structured interview schedule to assess the associated factors of malnutrition among early adolescent girls. Result: the study findings revealed that the prevalence of under nutrition was higher in rural area (40%) compared to urban (8.57%) whereas the prevalence of over nutrition was higher in urban (51.42%) compared to rural area (12.85%).There was significant association between prevalence of malnutrition with selected associated factors of malnutrition such as frequency of eating fast food, any past history of illness, engagement in physical activity. The study has several implications in Nursing practice, education, administration, research. The studies concluded with recommendations for future intervention and improve policy intervention regarding prevention of malnutrition.